Anisotropy engineering of metal organic framework derivatives for effective electromagnetic wave absorption. (30th August 2021) - Liu, Guang; Wu, Chen; Hu, Lei; Hu, Xin; Zhang, Xuefeng; Tang, Jin; Du, Haifeng; Wang, Xinhua; Yan, Mi
Abstract: Anisotropy engineering serves as an effective method to achieve unique properties and enhanced performance of materials. Here MOF-71 and derivatives with tuned anisotropy have been achieved via facial tuning the proticity of the solvents, giving rise to nanoflake assemblies into bellows-, boat- and flower-like microstructures. Three anisotropy dimensions including Faceting, Aspect ratio and Arrangement have been proposed to describe the anisotropy of the assemblies, which are further evaluated by heterotype ( H ¯ ), flatness ( F ¯ ) and orderliness ( O ¯ ). Combined off-axis electron holography and electromagnetic scattered field simulation visualize uniform distribution of magnetic lines due to enhanced anisotropy of the bellows-like derivatives. This gives rise to strengthened magnetic loss and electromagnetic wave absorption for the anisotropy evolution from the flower-, boat-to bellows-like structure. As such the work not only provides versatile strategy for anisotropy engineering and reification of the anisotropy for complicated assembled structures, but also insights on impacts of the anisotropy on the distribution of stray field, magnetic dipoles and scattered field for the design of electromagnetic absorbers, which are extendable to various areas including but not limited to magnetics, electrics and optics. Graphical abstract: Image 1 Highlights: Versatile strategy for anisotropy engineering has been provided. Evaluation for the anisotropy of complicated assembled structures has been proposed. Electron holography visualizes the stray field and distribution of magnetic dipoles. COMSOL simulations reveal the anisotropy effects on magnetic scattered field. Enhanced anisotropy contributes to enhanced magnetic loss and microwave absorption.